Breast cancer radiotherapy: exposure of the heart and lungs - Duane, F (2018)
Breast cancer radiotherapy can cause heart disease and lung cancer, with the risks increasing with the incidental radiation dose to the heart or lungs. To derive appropriate strategies for limiting the risks to future patients, detailed estimates of the radiation doses involved are required. Radiation-induced heart disease An atlas for cardiac substructure (segment) contouring on radiotherapy planning scans was developed. The atlas was used to estimate segment doses for 470 women irradiated in Denmark or Sweden during 1958-2001 who had developed ischaemic heart disease with known segment location of cardiac injury, thus enabling an assessment as to which segments are sensitive to radiation. Cardiac radiation doses were estimated for 771 women irradiated in the Netherlands during 1970 to 2009. The doses form the basis of three case-control studies characterising the relationship between cardiac dose and the risks of subsequent ischaemic heart disease, valvular heart disease and heart failure in young women (median age 50 years). Radiation-induced lung cancer Lung doses were estimated for ~40,000 women irradiated for breast cancer in 75 randomised trials. The doses were used to estimate the dose-response relationship for incident lung cancer. A systematic review of modern breast cancer regimens published worldwide during 2010-2015 was also performed. The modern typical doses found in these studies were combined with the estimated dose-response relationship to estimate absolute risks of lung cancer for women irradiated today. Irradiation of the internal mammary chain It has been recently shown that internal mammary chain irradiation improves survival but irradiating this region can expose the heart and lungs to several Gy radiation dose. To inform resource allocation, the percentage of women in one cancer centre who met current international criteria for IMC radiotherapy was investigated. Information on cardiovascular risk factors was also collected. Finally, a phase II clinical trial proposal was developed aiming to investigate if proton beam therapy reduces acute cardiac injury compared to modern X-ray treatment.